(untitled) (European Journal of Government and Economics, 2026)
This article applies Game Theory to diagnose persistent pathologies in public administration, such as bureaucratic inertia, as stable sub-optimal Nash Equilibria. Through a systematic literature review focused on the Greek context, it proposes a conceptual shift for public administration from a passive ’player’ to a proactive ’game designer’ who strategically alters incentives, rules, and information. The analysis reveals that this framework provides a practical roadmap for addressing deep-seated issues like tax evasion and inter-agency conflict by transforming dysfunctional equilibria. Ultimately, it offers an actionable model for designing effective reforms that can move complex administrative systems from deadlock toward sustainable cooperation.